Precanning and canning protocols for PSBRc 14 and PSBRc 60 - Ramos, Hazel Grace Borbon (2004)
ABSTRACT The study dealt with the utilization of the 2 test rice varieties, Philippine Seed Board Rice cultivar 14 and Philippine Seed Board Rice cultivar 60, for the production of canned rice product. Phase I dealt with the characterization of the rice cultivars in terms of amylose content, gelatinization temperature and gel consistency, parameters which were considered to have significant effects on the thermal resistance of the rice grain. Phase II focused on the applications of precanning procedures to temper the rice grains for thermal processing. The last stage of the study concentrated on the establishment of a thermal processing procedure to attain commercial sterility for the product. The PSBRc 14 test rice variety was established to have intermediate amylose content and intermediate-high gelatinization temperature. The PSBRc 60 variety, on the other hand, was characterized as grain with high amylose content and low gelatinization temperature. Both test rice varieties were established to have hard gel consistency. Soaking times of ≤7 min were required to reach the target moisture content of 30-35% for both test rice varieties during hydration of rice grains in aqueous acid solution. For the pregelatinization of hydrated rice grains, steaming times of ≤12 min at 80°C in aqueous acid were established to attain a moisture content level of 50-60% for both test rice varieties PSBRc 14 and PSBRc 60, respectively. The discrepancy in the thermal processing was attributed to the higher gelatinization temperature of PSBRc 14. The study recommended that rice grain to be used for thermal processing should have the following characteristics: high amylose content, high gelatinization temperature, and hard gel consistency. Precanning procedures including sequential washing with aqueous solution with a surface active agent and tap water, hydration of rice grains in aqueous acid solution and pregelatinization of hydrated rice grains by steaming using aqueous acid solution were recommended as appropriate precanning steps prior thermal processing of the test rice varieties because these allowed even gelatinization and retention of grain integrity during thermal processing.